Anti-Helicobacter pylori effect of the antioxidant extract from Baccharis trimera Less. (DC) - Otalíbio Castiglioni Nunes; Claudia Masrouah Jamal; Rodrigo Rezende Kitagawa; Rita de Cássia Ribeiro Gonçalves (International Journal of Phytomedicine, 2016)
One of the main risk factors for the development of stomach ulcers and cancer is infection with Helicobacter pylori bacteria, which is accompanied by considerable oxidative stress. Therefore, the aim of the present study was to assess the anti-Helicobacter pylori activity of B. trimera hydroalcoholic extract (HE) and aqueous (AqF), hexanic (HxF), and acetonitrile/chloroform (ACF) fractions, as well as their oxidant potentials. A preliminary phytochemical screening was carried out. Anti-Helicobacter pylori activity was assessed using a microdilution assay. After exposure to the investigated samples, the bacterial morphology was analysed under a scanning electron microscope (SEM). The antioxidant activity was evaluated in hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2 •- ), hypochlorous acid (HOCl), hydroxyl radical (HO • ) and nitric oxide (NO • ) assays. The highest concentration of polyphenols was found in HE, the highest concentration of flavonoids was found in ACF, and of tannins was found in AqF. In the anti-H. pylori assay, the MIC 90 was 512 µg/mL for HE and 1024 µg/mL for ACF, which was bactericidal. The SEM showed morphological alterations such as cell lysis in the tested samples. In the O 2 •- inhibition assay, the EC 50 of AqF was 5.85 ± 0.86. In the HOCl, HO • radical, NO • and H 2 O 2 scavenging assays, the best results were in ACF, with an EC 50 of 15.50 ± 0.80, 2.90 ± 0.48, 132.13 ± 7.38 and 66.70 ± 2.30 µg/mL, respectively. The analyses indicate that compounds present in B. trimera, especially in HE and ACF, are promising candidates for the prevention and treatment of diseases caused by H. pylori.